Interventions with milk proteins supplementation combined with exercise on musculoskeletal function in older adults with sarcopenia, osteoporosis and osteosarcopenia: a systematic review protocol of randomised controlled trials - Ricardo O Guerra; Mário Duarte Brito; Nailton José Neto; Cristiano dos Santos Gomes; Weslley Barbosa Sales; Gerlane Coelho Bernardo Guerra (BMJ Open)
Introduction Sarcopenia, osteoporosis and osteosarcopenia are conditions prevalent in ageing that impair muscle strength and bone density, increasing the risks of fractures, falls, disability and mortality. Recent studies highlight the benefits of milk protein supplementation (MPS) combined with exercises to improve musculoskeletal health in the older population. This systematic review protocol will enable the production of a compilation of evidence that will elucidate the effects of MPS combined with aerobic exercise, resistance exercise or both on the musculoskeletal function of older individuals with these three conditions.Methods/analysis Studies will be selected from electronic databases, including PubMed/MEDLINE, EMBASE, Scopus, Web of Science and the Cochrane Library, without restrictions on language or publication date. The outcomes evaluated will include muscle mass, muscle strength, BMD and physical performance after combined interventions of MPS and physical exercise of any type. The risk of bias will be assessed using the Cochrane Risk of Bias 2 tool. The Grading of Recommendations Assessment, Development and Evaluation approach will be used to classify the certainty of the evidence into four levels: high, moderate, low and very low. Meta-analysis will be performed given the homogeneity of the studies, using random effects methods in the face of the expected heterogeneity. The standardised mean difference (SMD) will be used for continuous data, and the I² index will assess heterogeneity (I² > 50%). Sensitivity analysis, ‘leave one out’ and a strategy for dealing with missing data will be carried out. Statistical analysis will be conducted using the STATA 18 software with a 95% CI and p<0.05. The searches will be carried out from inception until August 2025.Ethics and dissemination Formal ethical approval will not be required as primary data collection will not be performed. The results will be disseminated through peer-reviewed publications and presentations at conferences dedicated to the relevant field of study.PROSPERO registration number CRD42024555933.